Subjective Mental Workload Profile and Human Error Probability in Nurses: A Cross-sectional Analytical Study - Hadi Mirzabeigi; Vida Sadat Anoosheh; Masoud Rostami; Mahdi Jalali (International Journal of Environmental Health Engineering)
Aim: Medical errors cause serious and often preventable injuries to patients. This study aimed to identify and evaluate human errors to reduce their risk and its relationship with the subjective mental workload (SMWL) in nursing staff using the human error assessment and reduction technique (HEART). Methods: This cross-sectional analytical study was performed in one of the hospitals of Rafsanjan in Iran. First, task analysis was performed using the hierarchical task analysis method and nurses’ tasks were determined. Next, the human error probability (HEP) during the work for all tasks was determined with the HEART method. Finally, the factors and conditions that were effective in causing the errors were determined. Employees’ SMWL was also determined using the NASA-TLX index. Results: The mean ± standard deviation (SD) HEP score for nurse’s tasks was 1.79 ± 3.44. Results indicated a significant direct correlation between SMWL and HEP scores (r2 = 0.893, P < 0.0001). In addition, the mean rank of SMWL varied significantly across different human error groups based on the type of public duty (P < 0.001), indicating higher SMWL reported for tasks with elevated human error scores. Conclusion: The SMWL among the examined nurses was elevated, and it further increased during night shifts. In addition, there was a heightened HEP in certain nursing tasks. Given the increased SMWL and the potential for errors in complex tasks, it is crucial to prioritize that these responsibilities and implement control measures aimed at reducing the SMWL of the healthcare staff.